Plant components in the technology of meat products production - Shlapak, G; Agunova, L; Azarova, N (Вісник аграрної науки Причорномор'я, 2021)
Meat and meat products are a necessary source of a significant list of biologically active substances with high bioavailability, they are enriched with essential amino acids, vitamins, macro- and microelements. That is why the invention of new types of meat-based food products and the improvement of existing technologies for their production is an important task for scientists and specialists in the meat processing industry. A necessary direction in the production of new types of meat products is the synthesis of raw materials of animal and plant origin. Such a technological mechanism makes it possible to obtain food products that are enriched with organic nutrients that positively affect the functioning of the organs and systems of the human body and contribute to the rational use of raw materials of animal origin, which makes it possible to expand the range of products. Scientists and researchers of this field studied the possibility of adding various plant components to the composition of meat products and found their positive influence on structural-mechanical, organoleptic, functional-technological properties and biological value. Thus, the purpose of the study is to substantiate the use of a plant component, namely couscous groats from durum wheat varieties in the production technology of meat semi-finished products. The article substantiates and experimentally proves the possibility of using couscous groats in the production technology of chopped semi-finished products. According to the results of the study of functional-technological and organoleptic indicators of model minced meat, it was established that it is rational to add no more than 9% of prepared couscous to the recipe of meatballs made of beef and pork. According to the quality indicators, the semi-finished products meet the requirements of the current regulatory documentation